АГРОӨНЕРКӘСІПТІК КЕШЕННІҢ БӘСЕКЕГЕ ҚАБІЛЕТТІЛІГІН АРТТЫРУДАҒЫ МЕМЛЕКЕТ САЯСАТЫНЫҢ РӨЛІ ЖӘНЕ ОНЫ ІСКЕ АСЫРУ ӘДІСТЕРІ - Шеденов, Ө Қ; Дюсеханова, Н М (Journal of Economic Research & Business Administration, 2015)
In article is described about necessary from the government to adjust development of entering Agro-Industry Complex in number of the developed countries.